Funcionarios de Oficina de Recursos Humanos. (UNED, 2024)
Aparecen a la izquierda Edwin Matarrita Peña, Juan Elías Badilla Meléndez, Carlos Brizuela Ávila, Gustavo Amador Hernández-Jefe, Marvin Arce Jiménez, Marvin Zárate Jiménez, Juan Carlos Aguilar Rodríguez, Sentadas en el mismo orden, Lilliana Picado Alvarado, Marjorie Abarca Picado, Ana Lorena Carvajal Pérez, Ana Lorena Fallas Rivera, María Auxiliadora Torres Carvajal, Ana Lucía Chaves Madrigal, Mónica Reyes Sancho